Draft Annual Plan 1993-94 Vol-IV Government of Tripura - Planning Commission (Planning Commission, 1993)
It will be difficult for the existing State Institute of Education to meet the need of orientation of teachers key personnel resource persons and supervisors in View of the great change and multi-various expansion in the field of School End. It will therefore be essential to upgrade it to the level of SCERT as in other State and to expand it adequately so that it is able to meet the new challenges and coordinate the activities of the teacher training Institutes and DIETS and various orientation and training programmes and to implement innovative scheme
Planning and Coordination Department Government of Tripura
Planning and Coordination Department Government of Tripura